Effects of sorghum biomass quality on ensilability and methane yield. Issue 5 (24th February 2021) - Pasteris, Andrea M.; Zapka, Oliver; Plogsties, Vincent; Herrmann, Christiane; Heiermann, Monika
Abstract: Sorghum is currently being introduced in the temperate regions of Europe. It is characterized by good digestibility and high biomass yields, which make it a useful crop for anaerobic digestion. In this study, six commercial sorghum varieties comprising four different cultivars of  Sorghum bicolor L. Moench and two interspecific sorghum hybrids ( Sorghum sudanense L. ×  S. bicolor L. Moench) were harvested on two different dates during the years 2016 and 2017 at two diverse soil‐climate sites in Germany. The fresh harvested material and silages were analyzed to examine the ensilability of the different varieties with contrasting maturity characteristics. Subsequently, methane production experiments were performed to determine the specific methane yield (SMY) of the samples. The sorghum fresh matter (FM) varied among the sorghum types, including the parameters total solids (TS; 22.69%–46.93%FM), water‐soluble carbohydrates (2.68%–11.38%TS), and nitrates (0%–0.35%TS). The excellent ensiling ability of all the sorghum types analyzed was confirmed by evaluating the fermentation profile (pH range of 3.7–4.6; dominant presence of lactic acid [LA]; acetic acid [AA] in the range of 0.70%–2.38%TS; insignificant amount of butyric acid). The SMY ranged between 231.25 and 321.31 Ln  kg −1  VS and tended to decrease with the increasing harvest time and maturity. LA and AA were positively correlated with the SMY, while the neutral detergent fiber content was negatively correlated with it. The SMY—a key parameter reflecting the crop biomass quality for biogas production—was slightly higher for  S. bicolor than for the sorghum hybrids. However, the results of this study confirmed that if the final purpose is biomethanation, the ensilability of different sorghum types imposes no restriction. Furthermore, different sorghum types offer a wide harvest window, which can be useful for cropping schemes, ensiling, and methane production. Abstract : Sorghum has recently attracted attention in temperate regions of Europe as a suitable crop for anaerobic digestion. In this study, six commercial sorghum varieties with contrasting maturity tendencies were harvested in Germany. The fresh material characteristics, silage profile, and specific methane yield were analyzed and compared among the varieties. The results confirm that if the final purpose is biomethanation, the ensilability of different sorghum types imposes no restriction. In addition to this advantage, different sorghum types offer a wide harvest window, which can be useful for cropping schemes, ensiling, and methane production.